Improving Students’ Ability in Speaking Skill by Using Video-Based Storytelling - Rezeki, Heva Seri; Rizka, Budi; Yusnida, Dara (JETLi: Journal of English Teaching and Linguistics, 2023)
Speaking is the first way to interact with others in the social community. Furthermore, the success in learning a language at first can be seen from the ability of the learner’s speaking. However, it is very hard for the beginners to speak the foreign language, especially English. Therefore, the researcher is interested in conducting research entitled Using Video-Based Storytelling Techniques to Improve Students' Speaking Skills. Because, this method is easier and faster for students to accept and they are able see firsthand what is shown in the story and it is easier to remember it and capture the meaning of the story that is displayed. Thus, this research aims to find out whether the use of digital story telling effective to improve students' speaking skill. This research was focused on speaking the effectiveness of using video-based storytelling to improve the students’ speaking skill. This research applied a pre-experimental research design. The researcher used a purposive sampling method and took only class IX the sample of the research which consisted of 20 students. In addition, the researcher applied an instrument of this research namely oral test. In pre-test and post-test, the researcher gave topics through digital storytelling to stimulate the students to speak in front of the class. In pre-test and post-test, the students, one by one, speak each other with the researcher in the class. After pre-test, the researcher implemented a media of teaching speaking namely video-based storytelling as a treatment then the result of post-test was compared with the result of the students’ pre-test. The result found that the significant improvement of the students’ speaking ability. The score of grammar in expressing ideas was improved (150%) from the mean score 1 in pre-test to be 2.5 in post-test. The score of vocabulary in expressing ideas was improved (145%) from the mean score in pre-test 1.1 to be 2.7 in post-test. The score of comprehension in expressing ideas was improved (147%) from the mean score 1.05 in pre-test to be 2.6 in post-test. The score of fluency in expressing ideas was improved (150%) from the mean score 1.1 in pre-test to be 2.5 in post-test. The score of pronunciation on in expressing ideas was improved (108%) from the mean score in pre-test 1.2 to be 2.5 in post-test. It was proved by looking the percent improvement pre-test and post-test in grammar was 150%, in vocabulary 145%, in comprehension 147%, in fluency 150%, and in pronunciation 108% it means the students’ speaking improved after teaching speaking by using Video-based storytelling as media. The result of post-test can be improved from poor level to the average level and good level of classified.